The Importance of Rental House Tax in Increasing Regional Original Income Receiving at the Regional Tax and Retribution Service Agency of Dogiyiai Regency - Mjesfa, Adrian; Rahanra, Roy Marthen (Budapest International Research and Critics University, 2021)
Based on the results of data analysis obtained directly in the field, it shows that the rental house tax applied by the Office of the Regional Tax and Levy Service Agency of Dogiyai Regency has not run as expected, especially in terms of tax collection by officers, Regional Original Revenue has been running quite well. The problem is that employee discipline is still low. From these results it was concluded that the Head of BP2RD Dogiyai Regency, should be able to apply the importance of rental house taxes that are adjusted to the conditions of the subordinates and the work environment of the organization, so that employees can be motivated by the infrastructure provided by the leader so that they can work more productively.